Representação social do trabalho no Brasil na perspectiva do migrante haitiano - Anjos, Nara Angela dos Anjos (2017)
The aim of this research is to identify the social representations of Haitian migrants and work in Brazil. To better suit Haitian's everyday life, it was measured by the Social Psychology Community. The theory used as the basis of the study was the Social Representation's Theory, which allowed an accurate measurement of shared thoughts. The research was performed by questionnaire and by asking three leading questions. The leading questions were regarding what they thought about the work in Brazil before they migrated, and their thoughts at the present time while living in Brazil and what they had imagined to their future. The participants were fifteen Haitians and the research happened at Federal University of Parana and Service Center of Immigrants, in Curitiba/PR’s classroom. The questionnaire’s answers were subjected to SPSS program and descriptively analyzed. The interview’s content was analyzed by IRaMuTeQ’s program. The thought formed and shared about the work in Brazil was changing over time. The results of the inductive questions were: a) before migrating, they imagined many opportunities and high salaries. b) in Brazil, facing significant difficulties of heavy work hours and low salaries. c) What they think for the future is the hope they have for a better future, with a desired job and the family present. The interview’s contribution can raise civil society awareness and reach out to decision makers in the elaboration of public policies in order to improve reception and services for the Haitians migrants.